Phase change materials in solar photovoltaics applied in buildings: An overview - Mahian, Omid; Ghafarian, Sahar; Sarrafha, Hamid; Kasaeian, Alibakhsh; Yousefi, Hossein; Yan, Wei-Mon (Solar energy, 2021)
Building sector is responsible for approximately 40% of global carbon dioxide emission. Accordingly, any measures for reducing building energy consumption or providing it with renewable sources would substantially benefit sustainable development. A major approach towards this goal could be the application of photovoltaic modules in buildings, which could be conducted in various configurations. Integrating phase change materials with photovoltaic panels could simultaneously provide thermal regulation for the panel as well as thermal energy storage for the building. During the last two decades, research efforts on photovoltaic-phase change material systems for building applications have considerably grown. A systematic review of the current state of knowledge on photovoltaic-PCM modules applied in buildings could greatly benefit future research in this area. With this purpose in mind, the present study reviews the building applications of photovoltaic-phase change material units. The study aims to classify the existing literature on the field for acquiring a better understanding of the technological progress as well as identifying the existing gaps and future research prospects. Research attempts are categorized in four experimental, numerical, optimization, and economic sections. Each category is thoroughly analyzed and discussed in terms of current state of knowledge. Finally, technical analysis and possible future subjects are introduced and discussed.